Development of biodegradable plastic using Caulerpa Lentillifera’s extract for a sustainable environment - Syed Nasiruddin, Syed Taufiq Akmal; Abdul Hadi, Muhammad Firdaus; Kamaruddin, Sharir Aizat; Rajmi, Rozilah (Universiti Teknologi MARA, Kedah, 2022)
Due to the rise in the use of products made of plastic, the demand for plastic has increased, placing additional strain on the waste management system. There is much interest in reducing the usage of plastics made from petroleum, which pollute the environment on a large scale. One of the solutions to tackle the issues is to replace conventional plastics obtained from the petrochemical process with biodegradable plastic derived from natural resources such as raw agricultural waste, aquatic life, and even microbes. All these efforts aim to meet the global bioplastics and biopolymer goals. This study emphasizes one aquatic life, most notably known as sea grape or Caulerpa lentillifera, in stemming its potential to create a biodegradable plastic. Sea algae have a high nutritional value and are a vital source of dietary fibre, minerals, proteins, vitamins, and eicosatetraenoic acid (EPA). It also noted that Caulerpa lentillifera contains antibacterial properties, and it is found abundant on the east coast of Sabah and Malacca Strait and has economic importance in Malaysia. The innovation project aims to produce biodegradable plastic using Caulerpa lentillifera. This innovative product is expected to have high potential commercialization and benefit society. Awareness of using biodegradable plastic has increased recently because it has excellent biodegradable properties. In addition, it is easy to stretch, and its use can reduce the carbon footprint. Biodegradable plastic does not release carbon dioxide gas and indirectly reduces the greenhouse effect. Moreover, it does not generate much toxic emission and can biodegrade into a harmless natural component that mixes with the soil. Further, biodegradable packaging has been used in agriculture, consumer goods, medical equipment, and automotive. Furthermore, this innovative idea is consistent with the Sustainable Development Goals established by the United Nations SDG 14: "Life below water”.